The EFSUMB Guidelines and Recommendations for the Clinical Practice of Elastography in Non-Hepatic Applications: Update 2018 - Săftoiu, Adrian; Gilja, Odd Helge; Sidhu, Paul S.; Dietrich, Christoph F.; Cantisani, Vito; Amy, Dominique; Bachmann-Nielsen, Michael; Bob, Flaviu; Bojunga, Jörg; Brock, Marko; Calliada, Fabrizio; Clevert, Dirk André; Correas, Jean-Michel; D’Onofrio, Mirko; Ewertsen, Caroline; Farrokh, André; Fodor, Daniela; Fusaroli, Pietro; Havre, Roald Flesland; Hocke, Michael; Ignee, André; Jenssen, Christian; Klauser, Andrea Sabine; Kollmann, Christian; Radzina, Maija; Ramnarine, Kumar V.; Sconfienza, Luca Maria; Solomon, Carolina; Sporea, Ioan; Ștefănescu, Horia; Tanter, Mickael; Vilmann, Peter (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
This manuscript describes the use of ultrasound elastography, with the exception of liver applications, and represents an update of the 2013 EFSUMB (European Federation of Societies for Ultrasound in Medicine and Biology) Guidelines and Recommendations on the clinical use of elastography.
Keywords: ultrasound elastography; guideline; EFSUMB